The Effect of an Instructional Program of Critical Thinking Skills on Eleventh Grade Female Students' English Writing Skills in Jordan - Suha Abdul Razzaq Slim; Hamzah Ali Al-Omari (Deanship of Scientific Research (DSR), the University of Jordan, 2023)
Objectives: This study aimed at investigating the effect of implementing an instructional program based on critical thinking skills on developing English language writing skills among eleventh grade female students. Methods: A quasi experimental study approach was followed during the first semester of the scholastic year 2022-2023 in Wadi El Seir Directorate. The sample of the study consisted of 42 students in two sections who were randomly distributed to a control group (21 students) and to an experimental group (21 students). The two groups were examined by writing a composition to assess their writing skills which include the following higher thinking skills: analysis, decision making and expressing themselves through selecting one topic out of two. One research instrument was used to collect the data of the study; a comprehensive English achievement test of writing (Pre-posttest) assessed by a writing rubric that tests students' writing skills including the higher order skills. Data were analyzed using means, standard deviations, ANCOVA and MANCOVA. Results: The findings of the study indicated that there was a statistically significant difference (α=0.05) between the mean scores of both groups (experimental and control) regarding their English language writing skills. The mean score of the experimental group was (13.62 + 1.774) compared with the mean score of the control group was (9.29 + 1.774). The Writing achievement was in favour of the experimental group students. Conclusion: The study findings indicated that the instructional program based on critical thinking skills was significantly more effective than the conventional method in developing students' English language writing skills. The study recommends that English language writing skills should be improved through including the critical thinking skills in the English language curricula.